Assessment might dictate the curriculum, but what dictates assessment? - Dawson, Phillip; Bearman, Margaret; Boud, David J.; Hall, Matt; Molloy, Elizabeth K.; Bennett, Sue; Joughin, Gordon (Teaching and Learning Inquiry, 2013)
Almost all tertiary educators make assessment choices, for example, when they create an assessment task, design a rubric, or write multiple-choice items. Educators potentially have access to a variety of evidence and materials regarding good assessment practice but may not choose to consult them or be successful in translating these into practice. In this article, we propose a new challenge for the Scholarship of Teaching and Learning: the need to study the disjunction between proposals for assessment “best practice” and assessment in practice by examining the assessment decision-making of teachers. We suggest that assessment decision-making involves almost all university teachers, occurs at multiple levels, and is influenced by expertise, trust, culture, and policy. Assessment may dictate the curriculum from the student’s perspective, and we argue that assessment decision-making dictates assessment.